Modulation of human mesenchymal and pluripotent stem cell behavior using biophysical and biochemical cues: A review. Issue 2 (2nd September 2016) - Ding, Sheryl; Kingshott, Peter; Thissen, Helmut; Pera, Martin; Wang, Peng‐Yuan
ABSTRACT: In vitro manipulation of human stem cells is a critical process in regenerative medicine and cellular therapies. Strategies and methods to maintain stem cells and direct them into specific lineages are ongoing challenges in these fields. To date, a number of studies have reported that besides biochemical stimulation, biophysical cues in the form of surface patterning and external stimulation also influence stem cell attachment, proliferation, and differentiation, and can be used in cell reprogramming and the maintenance of pluripotency. While biochemical cues are generally effective and easy to deliver, biophysical cues have many other advantages for scalability as they are cost efficient, have a longer lifetime, and can be easily defined. However, different protocols and cell sources utilized in a variety of studies have led to difficulties in obtaining clear conclusions about the effects of the biophysical environment on stem cells. In addition, the examination of different types of external stimulation is time consuming and limited by available fabrication techniques, resulting in a delay in commercialization and clinical applications. In this review, we aim to summarize the most important biophysical cues and methods for the culture of human stem cells, including mesenchymal and pluripotent stem cells, to facilitate their adoption in stem cell biology. The standard classical protocols of using biochemical cues will also be discussed for comparison. We believe that combining biochemical and biophysical stimulation has the greatest potential to generate functionally mature cells at a scalable and inexpensive rate for diverse applications in regenerative medicine and cell therapy. Biotechnol. Bioeng. 2017;114: 260–280. © 2016 Wiley Periodicals, Inc. Abstract : The ability to manipulate human stem cells in vitro is vital in regenerative medicine and cellular therapies. While biochemical cues have been the focus of this area for some time, biophysical cues are emerging as a major factor in stem cell control. In this review, the authors summarize how different forms of biophysical stimulation influence stem cell behavior, and compare their effects to those of conventional culture methods.